Perlindungan Hukum Terhadap Perempuan dari Tindak Kekerasan Ditinjau dari Aspek Kesetaraan Gender : Implementasi, Hambatan dan Solusi dalam penerapannya - Raihan Malana Gibran; Ashar Fawazy; Sudirman Sitepu; Dwi Putri Lestarika (CV. ITTC INDONESIA, 2024)
This research discusses the legal protection of women from violence in Indonesia in the context of gender equality. Women in Indonesia are often victims of violence, both in the domestic and public spheres, with patriarchal culture dominating as one of the main factors. Although various laws and regulations exist to protect women, the implementation of the law still faces various obstacles, such as a lack of response to evolving forms of sexual violence, as well as legal interpretations that tend to blame the victim. This research uses a normative juridical method to analyze existing legal regulations, as well as to identify gaps in regulations that affect the protection of women's rights. An in-depth literature review was conducted of relevant laws, court decisions and agency reports, to assess the effectiveness of legal policies in providing appropriate protection. This research aims to identify more effective measures in the fight for gender equality and the protection of women through a more responsive and sensitive legal approach to gender issues. The results of the research are expected to contribute to the improvement of legal policies in Indonesia to further enhance the protection of women and realize gender equality.